Jejak-jejak Permukiman Kuno Di Kawasan Teluk Semangka, Propinsi Lampung - Yanti, Rus (KALPATARU, 2019)
AbstractPast communities occupied space for living in a wide variety of geographical conditions. Recentresearch in 2018, found the spreads of ancient settlement leads to the south to the bay in Tanggamus. How is the pattern of this dispersal and where their positions within historical context of Lampung are important to unearth due the lacking of information concerning this areas in the past, though the ancient cruise map are crossed to this land since long ago. The geoarchaeological survey in Tanggamus Bay found 15 ancient settlements lies in the alluvial and hilly lowland on the active fault of Semangka. Artifacts are dominant in Chinese and European ceramic fragments from the 19 ? 20 Centuries. This region is known as the Saibatin region clan which occupying the western, southern, and eastern regions of Lampung. Most of the sites are suspected of shifting to the eastern areas of the hills due to flooding seen from the distribution pattern of sites that are away from the rivers and near to the road as well as the lack of archaeological deposit which were found relatively from the current age of when Bantenese and the Dutch influenced in Lampung.Keywords: Settlement, Semangka Bay, Tanggamus.